Dialogue and Orthodox Mission Today - Mihăiţă, Nifon (International review of mission, 2013)
Dialogue and Orthodox mission are two fundamental aspects of contemporary Orthodoxy that characterize and qualify its ecclesiastic activity. Orthodoxy is open to ecumenical dialogue, as it believes in apostolicity and the truthfulness of its doctrine. Ecumenical involvement is both the fulfilment of Christ's will and a special occasion for the Orthodox Church to promote the richness and beauty of its spiritual legacy. The Orthodox mission focuses on all aspects and current needs of Orthodox believers, including the response to contemporary secular challenges. It is based on well-defined principles and it is systematic, its main aim being to promote our Lord's gospel.